Formulasi Dan Optimasi Sediaan Salep Luka Akut Berbasis Daun Wungu Graptophyllum Pictum L. Griff Dan Madu Klanceng - Tiwi Oktaviyani; Ratna Wijayatri; Eka Sakti Wahyuningtyas; Estrin Handayani; Sodiq Kamal (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2025)
Abstract: Acute wounds require quick and appropriate treatment to prevent complications such as infection and scar tissue formation. This study aims to develop and optimize an ointment formula based on Graptophyllum pictum L. Griff wungu leaf extract and klanceng honey, which is intended to prepare for the healing of acute wounds. Graptophyllum pictum L Griff leaves are known to have anti-inflammatory and antimicrobial properties, while klanceng honey is famous for its ability to accelerate tissue regeneration. The research process included the determination of Graptophyllum pictum L Griff leaves to ensure the authenticity of the ingredients, extraction using the maceration method with 96% ethanol and the manufacture of Graptophyllum pictum L Griff leaves ointment with concentrations of F1 10%, F2 7.5% and F3 5%. Evaluation of physical properties through a series of preparation tests to assess organoleptic, homogeneity, pH, dispersibility, adhesion, and stability. The optimization of the ointment preparation of the combination of Graptophyllum pictum L Griff leaves and klanceng honey showed that the ointment met all quality criteria as an ointment preparation intended for acute wounds, the preparation also had excellent stability. This research is expected to be the basis for the development of natural products for the treatment of acute wounds that are more effective, and safe to use.